The Translation of the Shakespearean Obscenity in As Alegres Comadres - Ramos, Elizabeth S. (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2018)
The comedy The Merry Wives of Windsor (1597-8) by William Shakespeare was written at a time when the codes of rudeness, obscenity and indecency were less stringent. At that time, some tolerance prevailed towards the obscene language inserted by the playwright in his production by means of double meanings, metaphors, allusions and puns. In the eighteenth and nineteenth centuries, due to the need to eliminate those constructions from a text that had become canonical, the Bard’s idolizers banned obscenity from Shakespearean language, arguing that its use had been due to the playwright’s desire to please less refined audiences. If, on one hand, that prevented Shakespeare’s work from exclusion from school textbooks and family shelves, on the other, it led translators to ignore expressions with which Shakespeare built his lewd comical images. The article thus proposes to expand the boundaries of thematic analysis of William Shakespeare’s texts to the (re)construction of the obscene language in the film As alegres comadres (2003), directed by the Brazilian filmmaker Leila Hipólito, as an adaptation of the comedy The Merry Wives of Windsor. Here, the film is understood as a rereading, allowing for questioning concepts such as authenticity, originality and hegemony, all so dear to a tradition that ignores the plurality of a cultural production and the inexhaustible condition of its plurality. Thus, the film is understood as a translation resulting from decisions made by Hipólito and her crew, which only in the realm of utopia could be identical with the Shakespearean text, for it encompasses the singularities of the translator. Throughout the article the term obscenity is used as a reference to the transgressing lexicon having to do with sexuality, being central to observe the solutions found by Leila Hipólito to recreate the Shakespearean lewdness in her filmic text.